Partograma e as dificuldades no preenchimento e utilização: uma revisão integrativa de literatura - ALMEIDA, Jéssica Samara Coelho de (2019)
The partogram is a graphical representation of labor, seen as an excellent visual resource for observing cervical dilation and fetal presentation in relation to time. It is a communication tool that helps to gain immediate knowledge of the evolution of labor and includes information on fetal heart rate, uterine size, drug use, and other important factors. Therefore, the partogram is essential for the follow up of the birth. However, it is observed that partograms are not always fulfilled in their totality. Thus, the present study aims to analyze the difficulties found by professionals who provide assistance to women in labor regarding the use and completion of partograph based on published articles. It is a literature-type research based on the search for articles published in full. The inclusion criteria used were: full text available, in the LILACS, SCIELO, MEDLINE and BDEnf database, in Portuguese, of the types articles, theses and monographs, from 2008 to 2018. After the bibliographic search, only 7 articles were part of the study because they provided more relevant information on the use of the partogram. For the analysis and discussion of the results found in the bibliographic survey, the following categories were elaborated: Insufficient knowledge about the partogram filling; Inadequate communication among professionals; Inadequate understanding of the importance of partograph and quality care; and difficulties in the use / completion of the Partogram by the professional attitude. After the discussion, it was concluded that the difficulties in the use and full filling of the partograph goes beyond just a difficulty in knowing how to fill out, involving many more factors. Therefore, although it is a obligation, it is still a challenge for the proper use of the partograph. Therefore, it is believed that this research was considered positive for the improvement of care, trying to unravel and ease the difficulties in using and filling the partograph.